Pengaruh Motivasi dan Kompensasi terhadap Disiplin yang Berdampak terhadap Kinerja Tenaga Kependidikan di Universitas Bangka Belitung - Alim Bahri; Afrizal Afrizal; Hamdan Hamdan (JEM Jurnal Ekonomi dan Manajemen, 2019)
This study is intended to analyze the effect of motivation and compensation on discipline that has an impact on the performance of the teaching staff at the University of Bangka Belitung. Respondents in this study were 189 people who were the educational staff. The analysis method uses path analysis. The results of this study produce that the motivation and compensation of each partially positive and significant effect on discipline and then discipline will affect the performance of the teaching staff at the University of Bangka Belitung. The recommendations of this study are expected to further enhance knowledge leaders in all fields and institutions provide support and appreciation to improve the performance of employees and lecturers.